Analisis Peran Unit Terminal Inspection Service dalam Pengawasan Fasilitas Landside pada Terminal Domestik Bandar Udara Internasional Juanda Surabaya - Wijayanto, Muhammad Mukti Bintang; Afriyanto, Dwi; Adriansyah, Feri; wijayanto, bintang (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The effectiveness of terminal facility supervision directly impacts user comfort and compliance with service standards mandated by airport regulations. This study aims to analyze the role of the Terminal Inspection Service (TIS) in supervising landside facilities at the Domestic Terminal of Juanda International Airport, Surabaya, and to identify the obstacles encountered during implementation. A qualitative approach with a case study design was employed. Data were collected through participant observation, in-depth interviews, and document analysis, then processed using the Miles, Huberman, and Saldaña interactive model, comprising data condensation, data display, and conclusion drawing and verification. The results indicate that the TIS unit conducts supervision through two approaches: proactive routine inspections and reactive complaint handling. Key challenges identified include limited personnel relative to the size of the area under supervision and delays in facility repairs due to a lack of available spare parts. The findings suggest that while the TIS unit's supervision generally aligns with the Minister of Transportation Regulation Number 41 of 2023, strengthening human resources and accelerating maintenance coordination are necessary to enhance the effectiveness of landside facility supervision.